Invierte.Pe and the Economic Benefits of Drinking Water Projects Using the Parametric Model - Rodríguez-Limachi, Omar Moisés; Incacutipa-Limachi, Duverly Joao; Ticona-Carrizales, Lucio; Yapuchura-Saico, Cristóbal Rufino; Huayta-Flores, Lenin; Campos-Segales, Betty; Maquera-Maquera, Yuselino (Journal of Posthumanism, 2025)
The objective of the research is to obtain the economic benefits of drinking water projects using the parametric logit model, from an Invierte.pe perspective. The methodology applied was the parametric contingent valuation model using the Logit model to estimate the willingness to pay (WTP), information was collected through the application of surveys to project users on their willingness or unwillingness to pay an amount of money for improvement of the drinking water supply service. The result was a WTP of 4.27 soles and economic benefits of the project for the first year of 314,511.00 soles and for the twentieth year of 370,080.00 soles. In conclusion, it is possible to incorporate in Invierte.pe the parametric logit model in the estimation of economic benefits of drinking water projects.